2020
DOI: 10.21203/rs.2.12094/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continuum of Sexual and Gender-Based Violence Risks among Syrian Refugee Women and Girls in Lebanon

Abstract: Abstract Background: A myriad of factors including socio-economic hardships impact refugees, with females being additionally exposed to various forms of sexual and gender-based violence (SGBV). The aim of this qualitative analysis was to understand and to provide new insight into the experiences of SGBV among Syrian refugee women and girls in Lebanon. Methods: The data are gained from a larger mixed-methods study, investigat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…In addition, early marriage was reported by Syrian refugees and key informants as a mechanism to alleviate the economic hardships of their families; however, only a few key informants reported that refugees resorted to sex work and begging in certain dire situations. Early marriage has been previously argued as a culturally acceptable practice among Syrians even prior to the war, a phenomenon that was further adopted by Syrian families post-displacement to overcome economic and security challenges and to give adolescent girls an improved and more secure life [54][55][56]. According to Bartels et al (2018), in many instances, Syrian refugee girls were ready to accept the proposals from well-settled men to secure more protection and escape the hardship conditions of their families [57].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, early marriage was reported by Syrian refugees and key informants as a mechanism to alleviate the economic hardships of their families; however, only a few key informants reported that refugees resorted to sex work and begging in certain dire situations. Early marriage has been previously argued as a culturally acceptable practice among Syrians even prior to the war, a phenomenon that was further adopted by Syrian families post-displacement to overcome economic and security challenges and to give adolescent girls an improved and more secure life [54][55][56]. According to Bartels et al (2018), in many instances, Syrian refugee girls were ready to accept the proposals from well-settled men to secure more protection and escape the hardship conditions of their families [57].…”
Section: Discussionmentioning
confidence: 99%
“…Syrian women in Lebanon face a continuum of SGBV risks, including public SGBV risks such as harassment and assault, and private SGBV risks such as child marriage, intimate partner violence, and domestic violence by their husbands' relatives (Roupetz et al 2020). The GBVIMS data highlights the most commonly reported forms of violence against Syrian refugees as being physical assault, domestic and sexual violence, denial of resources, and both child and forced marriage (Kevorkian 2016).…”
Section: Sgbv and Domestic Violence Prevalencementioning
confidence: 99%
“…The GBVIMS data highlights the most commonly reported forms of violence against Syrian refugees as being physical assault, domestic and sexual violence, denial of resources, and both child and forced marriage (Kevorkian 2016). Physical violence perpetrated by husbands was the most commonly reported form of intimate partner violence (IPV) among Syrian refugees (Roupetz et al 2020). IPV is thought to be exacerbated among displaced Syrian families due to the frustration men experience when their lives are disrupted, and traditional gender roles are challenged (El-Masri, Harvey and Garwood 2013).…”
Section: Sgbv and Domestic Violence Prevalencementioning
confidence: 99%
“…Galtung (1969) introduced the term “structural violence” to highlight the structures of inequality that comprise forms of violence, arguing that these can also lead to personal violence. For forced migrant women, such forms of violence can exist side by side as part of what has been described as a continuum of gender-based violence (Roupetz et al, 2020). Structural violence refers to harms that are preventable and where no one actor (person) commits the violence, but rather the harms emerge from inequality built into structures.…”
Section: Introductionmentioning
confidence: 99%